2015
DOI: 10.1118/1.4935201
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo dose verification method for SBRT–VMAT delivery using the EPID

Abstract: The authors have customized and validated a robust, physics-based model that calculates the delivered dose to a patient for SBRT-VMAT delivery using on-treatment EPID images. The accuracy of the results indicates that this approach is suitable for clinical implementation. Future work will incorporate this model into both offline and real-time clinical adaptive radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The diodes used in this study were the PTW 60017 Diode‐E (PTW, Freiburg, Germany) and the IBA SFD (IBA‐Scanditronix, Uppsala, Sweden). The Diode‐E is a diode detector designed for use in electron dosimetry while the SFD is a micro‐size sensitive volume detector used in small field dosimetry . The SFD is also suitable for electron dosimetry according to the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…The diodes used in this study were the PTW 60017 Diode‐E (PTW, Freiburg, Germany) and the IBA SFD (IBA‐Scanditronix, Uppsala, Sweden). The Diode‐E is a diode detector designed for use in electron dosimetry while the SFD is a micro‐size sensitive volume detector used in small field dosimetry . The SFD is also suitable for electron dosimetry according to the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…McCowan et al, calculations with AAA compared to CC result in a 2-5% lower lung dose, and up to 5% higher dose in the tissue where the radiation exits the lung (McCowan, Van Uytven, Van Beek, Asuni, & McCurdy, 2015). Latifi et al (2014) report statistically significant higher rates of local recurrences after SBRT of NSCLC calculated with PB compared to those calculated with CC; 21.5% (crude rate) with PB and 4.7% with CC.…”
Section: Dose Calculationmentioning
confidence: 98%
“…This method was shown to be as good as the accumulated dose calculated on the 4DCT phases for regular breathing motion, but better for irregular breathing motions. Another use of the EPID images was implemented by McCowan et al (2015), who created a model for reconstruction of the delivered dose using the EPID images acquired during treatment and Monte Carlo simulations of the fluence.…”
Section: Estimation Of Delivered Dosementioning
confidence: 99%
“…McCowan et al. have recently validated an in‐house physics‐based model which utilizes EPID images to reconstruct the dose in patient during SBRT‐VMAT treatments . The authors reported satisfactory results for lung and spine cases, with pass rates better than 93% with 3%‐3 mm γ ‐index tolerance level, showing the suitability of this approach for clinical implementation.…”
Section: Introductionmentioning
confidence: 99%